Parallelization of MLFMA with Composite Load Partition Criteria and Asynchronous Communication - Zhao, Huapeng; Hu, Jun; Nie, Zaiping (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper describes an efficient parallelization of the multi-level fast multipole algorithm (MLFMA) for fast solution of very large scale electromagnetic scattering problems. Computation in the MLFMA can be divided into several stages. To accomplish load balance at any time, load partition criteria are adjusted according to different features of every phase. Meanwhile, an asynchronous communication method is designed to overlap the communication with computation and thus the communication cost in parallelization is reduced. Numerical results show that good parallel efficiency is obtained in the presented parallelization of MLFMA. With our parallel MLFMA, a scattering problem with nearly 5, 300, 000 unknowns is solved in about six hours using 8 CPUs on SGI O350 server.